Employment Goals and Settings: Effects of Individual and Systemic Factors. (September 2018) - Nord, Derek; Hamre, Kristin; Pettingell, Sandra; Magiera, Louise
People with intellectual and developmental disabilities (IDD) continue to experience high rates of unemployment. Previous research suggests that including an employment goal in an individual's service plan can be a mechanism toward attaining employment, especially in a community setting. This study contributes to the understanding of the role of employment goals and employment in community and facility-based settings for people with IDD. This study used 2012 to 2013 National Core Indicators (NCI) Adult Consumer Survey data from 26 states to understand (a) the effect of disability and guardianship on attaining an employment goal and (b) the effect of disability, guardianship, and an employment goal on employment in community and facility-based settings. Results indicate that people with more significant intellectual disability (ID), communication and mobility challenges, and people under guardianship had significantly lower odds of an employment goal. Related to employment settings, people with an employment goal have significantly higher odds of employment in individual-community, odds ratio (OR) = 11.25, p ⩽ .001, and group-community (OR = 6.07, p ⩽ .001) settings. Those with more significant levels of ID had significantly lower odds of employment in individual-community (OR = 0.64, p ⩽ .001), group-community (OR = 0.85, p ⩽ .05), and facility-based settings (OR = 0.85, p ⩽ .01). The odds of employment for people with communication and mobility challenges were significantly lower, across all settings. Guardianship status did not have a significant effect. These findings have policy and practice implications that should be considered in systems improvement.